Deregulation and the current account - Philipp Harms (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2001)
This paper studies how removing barriers to competition in the nontraded goods sector affects the current account, the real exchange rate, and factor prices in a small open economy. We show that the expansion of the nontraded sector that results from a deregulation shock is associated with an accumulation of foreign assets unless production of nontraded goods is very capital-intensive. Moreover, while the real exchange rate decreases monotonically towards its new steady state, the real wage may temporarily overshoot its long-run level.
Keywords: D43; F32; F41; 330; deregulation; imperfect competition; current account; nontraded goods